Selecting patients for magnetic resonance imaging cognitive versus ultrasound fusion biopsy of the prostate: A within‐patient comparison. Issue 6 (5th June 2022) - Hayes, Mitch; Bassale, Solange; Chakiryan, Nicholas H.; Boileau, Luc; Grassauer, Jacob; Wagner, Matthew; Foster, Bryan; Coakley, Fergus; Isharwal, Sudhir; Amling, Christopher L.; Liu, Jen‐Jane
Abstract: Objectives: To compare overall agreement between magnetic resonance imaging (MRI)–ultrasound (US) fusion biopsy (FB) and MRI cognitive fusion biopsy (CB) of the prostate and determine which factors affect agreement for prostate cancer (PCa) who underwent both modalities in a prospective within‐patient protocol. Patients and Methods: From August 2017 to January 2021, patients with at least one Prostate Imaging Reporting & Data System (PI‐RADS) 3 or higher lesion on multiparametric MRI underwent transrectal FB and CB in a prospective within‐patient protocol. CB was performed for each region of interest (ROI), followed by FB, followed by standard 12 core biopsy. Patients who were not on active surveillance were analysed. The primary endpoint was agreement for any PCa detection. McNemar's test and kappa statistic were used to analyse agreement. Chi‐square test, Fisher's exact test and Wilcoxon rank sum test were used to analyse disagreement across clinical and MRI spatial variables. A multivariable generalized mixed‐effect model was used to compare the interaction between select variables and fusion modality. Statistics were performed using SAS and R. Results: Ninety patients and 98 lesions were included in the analysis. There was moderate agreement between FB and CB ( k  = 0.715). McNemar's test was insignificant ( p  = 0.285). Anterior location was the only variable associated with a significant variation in agreement, which was 70% for anterior lesions versus 89.7% for non‐anterior lesions ( p  = 0.035). Discordance did not vary significantly across other variables. In a mixed‐effect model, the interaction between anterior location and use of FB was insignificant ( p  = 0.411). Conclusion: In a within‐patient protocol of patients not on active surveillance, FB and CB performed similarly for PCa detection and with moderate agreement. Anterior location was associated with significantly higher disagreement, whereas other patient and lesion characteristics were not. Additional studies are needed to determine optimal biopsy technique for sampling anterior ROI.